Women's Empowerment Based on Local Wisdom (Karawo Cake Center, Tanggilingo Bone Bolango Village) - Nirmala Afrianti Sahi; Salma Rivani Luawo; Moh.Arif Novriansyah (Global Scientific Publishing, 2023)
Women have a big role in maintaining local culture and wisdom which through a series of processes will bring benefits to the community itself. This role is manifested in a woman's social activities in society or in actualizing herself in the environment in which she finds herself. Bone Bolango Regency is one of the regencies in Gorontalo Province which has very strong local wisdom both in the social and cultural fields and in the culinary food sector. Various typical Gorontalo flavors are found in Bone Bolango Regency, one of the villages that has human resources that make snack cakes. typical Gorontalo cakes and pastries and the typical Gorontalo cake kukisi Karwo, namely Tanggilingo Village. Tanggilingo Village is one of the villages in Kabila District, Bonebolango Regency which has potential human resources for making cakes or cookies in the Gorontalo language. Out of a population of 1,972 people, 35% of housewives have the expertise to make cookies from generation to generation, including wet cakes and pastries and Karawo cookies. which is a typical Gorontalo cake, the production volume in the month of Ramadan leading up to Eid al-Fitr was 15,000 jars of Karawo cookies, which had an impact on improving the economy of Tanggilingo Village. This research applies qualitative methods, where information is collected by means of interviews, observation of the required data, document studies and study of relevant literature. At the stage of reducing the data that has been obtained, presenting the data and carrying out discussions and drawing conclusions, the data is analyzed interactively. The results of this data analysis show that the dynamics of the development of karawo art can be observed using various points of view. This starts with karawo which is considered a commodity economic activity, a tourist attraction, to internal and external factors influencing the development of the karawo activity itself. . And Strengthening Innovation for Women is capital to prove that women can exist to maintain local wisdom in the region.
Keywords: Empowerment; Women; Local wisdom